2004
DOI: 10.1258/096914104774061056
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of conventional cytology: results from a multicentre screening study in India

Abstract: Objective:We conducted a multi-centre cross-sectional study in India to evaluate the accuracy of conventional cytology to detect high-grade squamous intraepithelial lesions (HSIL). Setting:Cross-sectional studies in Jaipur, Kolkata, Mumbai and Trivandrum, India, during 1999-2003. Methods: A common protocol and questionnaire were used to test 22,663 women aged 25-65 years with conventional cytology in ve cross-sectional studies. Three thresholds were used to de ne test positivity: atypical squamous cells of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 24 publications
7
53
2
Order By: Relevance
“…These findings are in concordance with the study of Shorey et al, who reported 96.8% smears as satisfactory and 3.3% as unsatisfactory. [13] Similar results of around 3.8% unsatisfactory smears were also reported by Sankaranarayanan R et al [14] On comparing the cytological findings of the Conventional system and the Bethesda system, inflammation was found to be the most common finding in both the systems. Nonspecific inflammation was seen in similar number of cases by both the systems of reporting i.e 85.2% by the Conventional method and 86.5% by the Bethesda system.…”
Section: Discussionsupporting
confidence: 72%
“…These findings are in concordance with the study of Shorey et al, who reported 96.8% smears as satisfactory and 3.3% as unsatisfactory. [13] Similar results of around 3.8% unsatisfactory smears were also reported by Sankaranarayanan R et al [14] On comparing the cytological findings of the Conventional system and the Bethesda system, inflammation was found to be the most common finding in both the systems. Nonspecific inflammation was seen in similar number of cases by both the systems of reporting i.e 85.2% by the Conventional method and 86.5% by the Bethesda system.…”
Section: Discussionsupporting
confidence: 72%
“…Although our results indicate that the visual tests have similar sensitivity to that of cytology, albeit with significantly lower specificity and positive predictive value, for detecting histologically confirmed high-grade CIN and invasive cancer when concurrently evaluated in research settings as observed in cross-sectional studies in the past, 18,19 cytology had a higher sensitivity than the visual tests to detect high-grade CIN that were positive for p16 INK4a overexpression and/or high-risk HPV types. The specificity of VIA and VILI were low, compared to that of cytology.…”
Section: Discussionmentioning
confidence: 53%
“…The screening process, along with the delays between screening, test results and ultimate treatment are major obstacles to the success of cytology-based programs in low-resource settings. Although cytology screening has been introduced in LMIC over the past 30 years, it has not resulted in the expected decreases in cervical cancer incidence and mortality similar to those observed in the HIC, primarily because of the above mentioned hurdles associated with low coverage of the target population (Dzuba et al, 2005 the CIN2 and CIN 3 (53% in HIC, and 26-65% in LMIC) (Almonte et al, 2007;Cuzick et al, 2006;Sankaranarayanan et al, 2004b;Sarian et al, 2005), repeated screening at regular intervals is necessary for the programmes to be effective. This low sensitivity in developed countries is overcome by organized periodic screening, which is not feasible with the opportunistic screening carried in low-resource setting.…”
Section: Cytologymentioning
confidence: 99%